EVALUATION OF TEACHERS' VIEWS ON THE EDUCATION OF SEASONAL AGRICULTURAL WORKER MOTHERS AND THEIR CHILDREN - Gülsün ŞAHAN (Fırat University, 2021)
The workers who will work in agriculture every year in our country migrate periodically with their families. School-age children of immigrant families start school late and have to leave early. This situation causes disruptions in the education of children. Education of children who migrate seasonally to work is not at the desired level. The responsibility of the family, especially the responsibility of the mothers, is important in the education of migrant children. It is known that children are more successful in families who care about the education of children. It was revealed in the exams that the children of educated mothers were more successful. The role of mothers is important in the education of the child. There is a need for studies not only for the education of children but also for the education of mothers. Education should be given not only to children but also in families. Starting from literacy education, families should be provided with education on health, agriculture and nutrition. The aim of this study is to reveal the educational problems of seasonal agricultural workers mothers and their children and to develop solutions according to the opinions of the teachers. The research was carried out in accordance with the case study, one of the qualitative research methods. In the research, the data collection tool is semi-structured interview forms created as a result of expert evaluation. The study included 11 primary and secondary schools in a district in Southeastern Anatolia, where seasonal migration was intense, and 11 teachers who worked or worked in the Vocational Training Center. In the study, it was concluded that seasonal agricultural worker families do not include studies on the education of mothers, there are difficulties in the mothers' coming to school, support education is insufficient for the children who leave school late, and the studies about their education are not at the desired level.